The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10653-013-9551-x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoisomeric profiling of pharmaceuticals ibuprofen and iopromide in wastewater and river water, China

Abstract: Stereoisomeric compositions can provide insights into sources, fate, and ecological risks of contaminants in the environment. In this study, stereoisomeric profiles of ibuprofen and iopromide were investigated in wastewater and receiving surface water of the Pearl River Delta, south China. The enantiomeric fraction (EF) of ibuprofen was 0.108-0.188 and 0.480, whereas the isomer ratio (IR) of iopromide was 1.426-1.673 and 1.737-1.898 in the influent and final effluent, respectively, suggesting stereoselective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…Although ibuprofen is marketed as a racemic mixture, only the active S‐(+)‐enantiomer was detected in influent wastewater samples (0.35 ± 0.09 μg l −1 ). It has been reported that R‐(−)‐ibuprofen undergoes chiral inversion during metabolism causing excess of the S‐(+)‐enantiomer in urine . This effect was reflected in this study in the higher concentrations of this enantiomer in influent wastewater.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…Although ibuprofen is marketed as a racemic mixture, only the active S‐(+)‐enantiomer was detected in influent wastewater samples (0.35 ± 0.09 μg l −1 ). It has been reported that R‐(−)‐ibuprofen undergoes chiral inversion during metabolism causing excess of the S‐(+)‐enantiomer in urine . This effect was reflected in this study in the higher concentrations of this enantiomer in influent wastewater.…”
Section: Resultscontrasting
confidence: 74%
“…It has been reported that R-(À)-ibuprofen undergoes chiral inversion during metabolism causing excess of the S-(+)-enantiomer in urine. [23,[35][36][37] This effect was reflected in this study in the higher concentrations of this enantiomer in influent wastewater. Interestingly, both ibuprofen metabolites were detected in influent wastewater with excess of the first eluted enantiomer (EF of carboxyibuprofen 0.83 AE 0.01; EF of 2hydroxyibuprofen 0.76 AE 0.01).…”
Section: Application To Environmental Samplesmentioning
confidence: 51%
“…It can be postulated that the presence of dissolved organic matter of comparatively high concentration, as well as particulates in environmental waters will reduce EC degradation kinetics by clouding sunlight intensity. However, West and Rowland (2012) found that humic acid (a small molecular weight charged species) slowed or increased degradation rate, dependant on the specific EC investigated. Increased degradation in the presence of humic acid or nitrates can be attributed to indirect photolysis (Andreozzi et al, 2003).…”
Section: Physicochemical Processesmentioning
confidence: 97%
“…It should be noted that collated toxicological response information only gives a subjective insight into toxicity as this is highly dependent on the test species studied as ECs can cause varying toxicological responses between species type. Data obtained from: (Henschel et al, 1997;Holten Lü tzhøft et al, 1999;Wollenberger et al, 2000;Cleuvers, 2003;Ferrari et al, 2003;Pro et al, 2003;Cleuvers, 2004;Eguchi et al, 2004;Pomati et al, 2004;Cleuvers, 2005;Isidori et al, 2005a,b;Heckmann et al, 2007;Isidori et al, 2007;Kim et al, 2007;DeLorenzo and Fleming, 2008;Park and Choi, 2008;Quinn et al, 2008b;De Liguoro et al, 2009;Rosal et al, 2010;Han et al, 2010;Van den Brandhof and Montforts, 2010;Dave and Herger, 2012). EC 50 's classified as <1 mg l ¡1 ¼ very toxic to aquatic organisms, 1e10 mg l ¡1 ¼ toxic to aquatic organisms, 10e100 mg l ¡1 ¼ harmful to aquatic organisms and >100 mg l ¡1 ¼ not classified (Commission of the European Communities, 1996;Cleuvers, 2003).…”
Section: Illicit Drugsmentioning
confidence: 99%
“…[70] In addition, the degree to which heavy metal cations complex with organic materials is affected by the pH of the environment. [71,72] Additional challenges are also present when using a polymeric sensing material. Some polymeric materials may shrink or swell with varying pH, which can affect the sensitivity and selectivity of the material.…”
Section: Phmentioning
confidence: 99%